Utilization of Betadine as an Indicator of the Presence of Vitamin C (Ascorbic Acid) In Fruits and Vegetables - Tariza Humaira Tembusai; Annisa Tri Banoeari; Riris Mandaoni Siahaan (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
This study aims to find out whether or not there is a content of vitamin C in tomatoes, cucumbers, chayote, spinach, lime and bilimbi by reacting with betadine containing povidone iodine 10% w/v, which is equivalent to 1% iodine. If iodine reacts with vitamin C, then the color of iodine will disappear. Each extract of fruits and vegetables is added to a glass containing aqua that has been added 25 drops of betadine with a solution color that is reddish brown. Obtained discoloration from each addition of fruit and vegetable extract: a) Cucumbers change color to solid bright yellow, b) Tomatoes change color to clear bright yellow, c) Chayote change color to white, d) Spinach changes color to dark green, e) Lime changes color to brownish orange and f) Bilimbi changes color to orange. The discoloration that occurs indicates that tomatoes, cucumbers, chayote, spinach, lime and bilimbi contain vitamin C.